Asymmetric impact of the oil price changes on stocks market for selected ASEAN countries / Shahiszan Ismail ... [et al.] - Ismail, Shahiszan; Mohd Sidek, Noor Zahirah; Mohamad Yunus, Fauziah; Laidin, Jamilah; Ismail, Nor Azira (2021)
This paper complements a growing literature of stock market to reach several objectives. First, to investigate the asymmetric impact of oil price changes on stock market by focusing on selected ASEAN countries. The next objective is to compare the different impact on changes in stock price effect from current situation of pandemic Covid-19. Using daily data from year 2019 until 2020, the results can be explained by the NARDL model in which independent variable are decomposed into its positive and negative partial to determine the long-term and short-term relationship. The empirical findings would help economic players to diversify their portfolios across selected ASEAN countries to minimize risks and maximize returns.